3-D adaptive FEA with weighted node density technique. Issue 5 (21st July 2020) - Yamaguchi, Tadashi; Kawase, Yoshihiro; Ishimura, Shota
Abstract : Purpose: This paper aims to propose a method to create 3-D finite element meshes automatically using the Delaunay tetrahedralization with the weighted node density technique. Using this method, the adaptive finite element analysis (FEA) was carried out for the calculation of the magnetic field of an eddy current verification model to clarify the usefulness of the method. Moreover, the error evaluation function for the adaptive FEA was also discussed. Design/methodology/approach: The method to create the 3-D finite element meshes using the Delaunay tetrahedralization is realized by the weighted node density technique, and Zienkiewicz-Zhu's error estimator is used as the error evaluation function of the adaptive FEA. Findings: The magnetic flux density vectors on the node in the error evaluation function for the adaptive FEA should be calculated with the weighted average by the reciprocal of the volume of elements. Originality/value: This paper describes the method to create 3-D finite element meshes and the comparison among calculation methods of the magnetic flux density vectors on the node for the error estimator.